Rynek ubezpieczeniowy wciąż zagrożony przestępczością - Filipowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2008)
The article is devoted to numerous threats to insurance market. Statistical data at the disposal of insurance companies and the police do not reflect actual criminal threat and losses of insurance companies. The problem, recognised as it is, cannot be ignored due to insurance sector’s significance in national economy. An ever increasing number of instances of insurance frauds, variety of their form and difficulties in their detection not only causes economic losses but also indirectly affects insurance companies’ service and attitude to claimants.The causes of the increasing problem deserve profound analysis: do they result from legislation or the attitude of law enforcement to this type of offence or the attitude of insurance companies? The situation validates the claim that insurance frauds deserve both prevention and penalisation in order to prevent economic losses suffered both by insurance companies and their clients. The issue is significant and interesting, combining economic, social and legal aspects, in a sense reflecting the stage in the development of the society.
Keywords: rynek ubezpieczeniowy; przestępstwa ubezpieczeniowe